Limited value of serum neutrophil-to-lymphocyte ratio in the diagnosis of chronic periprosthetic joint infection - Ye, Yongyu; Chen, Weishen; Gu, Minghui; Liu, Qiaoli; Xian, Guoyan; Pan, Baiqi; Zheng, Linli; Chen, Xiaoling; Zhang, Ziji; Sheng, Puyi (Journal of orthopaedics and traumatology, 2021)
Background Diagnosing chronic periprosthetic joint infection (PJI) is challenging. No single biomarker can accurately recognize PJI preoperatively in a timely manner. Therefore, the aim of the present study was to investigate the usefulness of the serum neutrophil-to-lymphocyte ratio (NLR) in aiding the diagnosis of chronic PJI. Materials and methods We retrospectively evaluated the medical records of 158 patients who had undergone revision arthroplasty (104 with aseptic mechanic failure and 54 with chronic PJI) from July 2011 to July 2020. Univariate analysis followed by multivariate logistic regression was applied to compare NLR, C-reactive protein (CRP), and erythrocyte sedimentation ratio (ESR) between the two groups. The receiver operating characteristic (ROC) curve was used to assess the diagnostic performance of NLR alone and in combination with CRP and ESR. Results NLR, CRP, and ESR were significantly higher in patients with chronic PJI than in the aseptic revision group ( p < 0.05). ROC curve analysis revealed that NLR had a sensitivity of 57.41% and a specificity of 77.88% with an optimal threshold of 2.56. The optimal threshold for CRP and ESR was 7.00 mg/L (sensitivity 62.50% and specificity 83.12%) and 43 mm/h (sensitivity 59.38% and specificity 80.52%), respectively. The combined diagnostic value of NLR with CRP and ESR was shown to have no additional diagnostic value in predicting chronic PJI. Conclusion Compared with traditional inflammatory biomarkers (ESR and CRP), the value of serum NLR alone or combined with CRP and ESR for diagnosing chronic PJI is limited. Level of evidence Level 3.